Selection of Numerical Criterion Value for Determination of Short Circuit Type in Adaptive Micro-Processing Current Protection of Electric Power Lines - A. V. Kovalevsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a principle for determination of a short circuit type which is used in the mathematical model of adaptive micro-processing protection with the purpose to improve sensitivity. As a result of a calculative experiment dependences ΔI(t) for various short circuit types (three- and two-phase short circuits) have been obtained at a number of points of the investigated power network. These dependences make it possible to determine a numerical value of ΔI coefficient. A comparative analysis has been made to study an operation of adaptive and non-adaptive microprocessing protections in the case of asymmetric damages of the investigated power network just in the same points.